Neuroprotective effects of oxysophocarpine on neonatal rat primary cultured hippocampal neurons injured by oxygen-glucose deprivation and reperfusion. (August 2014) - Zhu, Qing-Luan; Li, Yu-Xiang; Zhou, Ru; Ma, Ning-Tian; Chang, Ren-Yuan; Wang, Teng-Fei; Zhang, Yi; Chen, Xiao-Ping; Hao, Yin-Ju; Jin, Shao-Ju; Ma, Lin; Du, Juan; et al.
Abstract Context: Oxysophocarpine (OSC), a quinolizidine alkaloid extracted from leguminous plants of the genus Robinia, is traditionally used for various diseases including neuronal disorders. Objective: This study investigated the protective effects of OSC on neonatal rat primary-cultured hippocampal neurons were injured by oxygen–glucose deprivation and reperfusion (OGD/RP). Materials and methods: Cultured hippocampal neurons were exposed to OGD for 2 h followed by a 24 h RP. OSC (1, 2, and 5 μmol/L) and nimodipine (Nim) (12 μmol/L) were added to the culture after OGD but before RP. The cultures of the control group were not exposed to OGD/RP. MTT and LDH assay were used to evaluate the protective effects of OSC. The concentration of intracellular-free calcium [Ca2+]i and mitochondrial membrane potential (MMP) were determined to evaluate the degree of neuronal damage. Morphologic changes of neurons following OGD/RP were observed with a microscope. The expression of caspase-3 and caspase-12 mRNA was examined by real-time quantitative PCR. Results: The IC50 of OSC was found to be 100 μmol/L. Treatment with OSC (1, 2, and 5 μmol/L) attenuated neuronal damage (p < 0.001), with evidence of increased cell viability (p < 0.001) and decreased cell morphologic impairment. Furthermore, OSC increased MMP (p < 0.001), but it inhibited [Ca2+]i (p < 0.001) elevation in a dose-dependent manner at OGD/RP. OSC (5 μmol/L) also decreased the expression of caspase-3 (p < 0.05) and caspase-12 (p < 0.05). Discussion and conclusion: The results suggested that OSC has significant neuroprotective effects that can be attributed to inhibiting endoplasmic reticulum (ER) stress-induced apoptosis.